Chronomobility of international students under COVID-19 Australia - Dhanji, Surjeet D.; Ohashi, Jun; Song, Jay (Frontiers in Sociology, 2023)
This article investigates the chronomobility of international students in Australia going through COVID-19. Existing literature on international students approaches them largely in two manners: a market or victims. Using Shanti Robertson's chronomobility, the study focuses on international students' coping mechanisms and strategies for their next moves. Drawing from 15 in-depth interviews with international students formally enrolled in Australian institutions in Melbourne, the longest lockdown city during the pandemic, the authors find various ways of short-term coping mechanisms through meditation, physical exercises, virtual escapism and counselling. Furthermore, despite pandemic immobility, students presented a high level of resilience in making future decisions for post-pandemic mobilities. We conclude that family support and social networks are key to realise full potentials of international students as skilled migrants and valued members of society.Our manuscript contributes to the field of migration and mobility by enriching Robertson's concept of chrono-mobility and adding the empirical case study from international students in Australia during the latest pandemic in 2020-2021.Our manuscript contributes to the field of migration and mobility by enriching Robertson's concept of chrono-mobility and adding the empirical case study from international students in Australia during the latest pandemic in 2020-2021.Generated Statement: No animal studies are presented in this manuscript.Generated Statement: The studies involving humans were approved by University of Melbourne Human Ethics Committee. The studies were conducted in accordance with the local legislation and institutional requirements. The participants provided their written informed consent to participate in this study.Generated Statement: Written informed consent was obtained from the individual(s) for the publication of any potentially identifiable images or data included in this article.